From bench to bedside, boswellic acids in anti-inflammatory therapy — mechanistic insights, bioavailability challenges, and optimization approaches - Peng, Chuhang; Yang, Yujia; Wang, Yuzhi; Gong, Bao; Sun, Xiuting; Yang, Xinquan (Frontiers in Pharmacology, 2025)
Boswellic acids (BAs), a group of pentacyclic triterpenoids derived from the gum resin of Boswellia species, exhibit promising anti-inflammatory potential through diverse mechanisms. This review provides a comprehensive and structured summary of BAs’ anti-inflammatory actions, spanning key signaling pathways including NF-κB, MAPK, 5-LOX, COX-2, and NLRP3 inflammasome, as well as their modulation of cytokines, immune cell activity, and oxidative stress. We further highlight recent progress in molecular docking and dynamic simulations that elucidate BA–protein interactions at the structural level. The review integrates evidence from preclinical and clinical studies, with detailed pharmacological parameters such as model types, dose ranges, and control settings. Challenges related to BAs’ poor solubility and limited bioavailability are critically addressed. Recent advances in delivery systems, including nanoparticles, micelles, phytosomes, and ligand-targeted carriers—are summarized with mechanistic insight. Safety, toxicity, and formulation limitations are also discussed to provide a balanced perspective on their clinical translation. Overall, this review aims to clarify how BAs exert multi-target immunomodulatory effects and proposes directions for future research and therapeutic development.